2014
DOI: 10.1002/cne.23639
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionarily conserved organization of the dopaminergic system in lamprey: SNc/VTA afferent and efferent connectivity and D2 receptor expression

Abstract: The dopaminergic system influences motor behavior, signals reward and novelty, and is an essential component of the basal ganglia in all vertebrates including the lamprey, one of the phylogenetically oldest vertebrates. The intrinsic organization and function of the lamprey basal ganglia is highly conserved. For instance, the direct and indirect pathways are modulated through dopamine D1 and D2 receptors in lamprey and in mammals. The nucleus of the tuberculum posterior, a homologue of the substantia nigra par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
103
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(113 citation statements)
references
References 91 publications
(162 reference statements)
10
103
0
Order By: Relevance
“…In lamprey (Ryczko et al, 2013) and salamander (Ryczko et al, 2016a), dopaminergic fibers were found around MLR cholinergic cells, a conserved landmark of the MLR (see Ryczko and Dubuc, 2013). We identified the origin of this dopaminergic innervation in lamprey (Figure 2G, Ryczko et al, 2013; see also Perez-Fernandez et al, 2014) and in salamander (Figure 2H, Ryczko et al, 2016a) as a diencephalic dopaminergic region called the posterior tuberculum. This region sends ascending projection to the striatum, and is considered homologous to the mammalian SNc and/or ventral tegmental area (Marin et al, 1997; Pombal et al, 1997; Puelles and Verney, 1998; Smeets et al, 2000; Rink and Wullimann, 2001; Blin et al, 2008; for review see Yamamoto and Vernier, 2011; Wullimann, 2014).…”
Section: A New Descending Dopaminergic Pathway Has Been Unraveledmentioning
confidence: 81%
See 1 more Smart Citation
“…In lamprey (Ryczko et al, 2013) and salamander (Ryczko et al, 2016a), dopaminergic fibers were found around MLR cholinergic cells, a conserved landmark of the MLR (see Ryczko and Dubuc, 2013). We identified the origin of this dopaminergic innervation in lamprey (Figure 2G, Ryczko et al, 2013; see also Perez-Fernandez et al, 2014) and in salamander (Figure 2H, Ryczko et al, 2016a) as a diencephalic dopaminergic region called the posterior tuberculum. This region sends ascending projection to the striatum, and is considered homologous to the mammalian SNc and/or ventral tegmental area (Marin et al, 1997; Pombal et al, 1997; Puelles and Verney, 1998; Smeets et al, 2000; Rink and Wullimann, 2001; Blin et al, 2008; for review see Yamamoto and Vernier, 2011; Wullimann, 2014).…”
Section: A New Descending Dopaminergic Pathway Has Been Unraveledmentioning
confidence: 81%
“…The multiple alterations in the MLR in PD are compatible with such phenomenon (see Fornito et al, 2015). The reciprocal projections between the SNc and the PPN (McGeer and McGeer, 1984; Lavoie and Parent, 1994; Ryczko et al, 2013, 2016a; Perez-Fernandez et al, 2014) could also contribute to potentiate the transneuronal degeneration process. Nigral dopamine cell degeneration would cause a loss of the dopaminergic input to the MLR, causing MLR cells to degenerate.…”
Section: Possible Role Of the Descending Dopaminergic Pathway In Pdmentioning
confidence: 99%
“…To what extent the basal ganglia influence processing in tectum by disinhibition of local GABAergic neurons is as yet not clear. There is also in lamprey a dopaminergic projection from the substantia nigra pars compacta, which will potentiate (via dopamine D 1 receptor) or suppress (via dopamine D 2 receptor) the responses of the tectal output neurons (62,63). Finally, there is cholinergic input from the parabigeminal nucleus (isthmic nucleus in nonmammals) that can modulate the visuomotor pathway through projections to the superficial layer (59,64).…”
Section: Discussionmentioning
confidence: 99%
“…In lampreys, only a few meso-diencephalic DA neurons send ascending projections to the striatum (9,22); the majority of DA neurons send a direct descending projection to the MLR (22,23), where DA is released and increases locomotor output through D1 receptors (22). These results demonstrate that the descending dopaminergic pathway to the MLR is an important modulator of locomotor output, but it remains to be determined whether this pathway is conserved in higher vertebrates.…”
mentioning
confidence: 87%